Expression of the K+/Cl− cotransporter, KCC2, in cerebellar Purkinje cells is regulated by group-I metabotropic glutamate receptors. (15th March 2017) - Notartomaso, Serena; Mascio, Giada; Scarselli, Pamela; Martinello, Katiuscia; Fucile, Sergio; Gradini, Roberto; Bruno, Valeria; Battaglia, Giuseppe; Nicoletti, Ferdinando
Abstract: The neuronal K + /Cl − symporter, KCC2, shapes synaptic responses mediated by Cl − -permeant GABAA receptors. Moving from the evidence that excitatory neurotransmission drives changes in KCC2 expression in cerebellar neurons, we studied the regulation of KCC2 expression by group-I metabotropic glutamate (mGlu) receptors in the cerebellum of adult mice. Mice lacking mGlu5 receptors showed a large reduction in cerebellar KCC2 protein levels and a loss of KCC2 immunoreactivity in Purkinje cells. Similar changes were seen in mice treated with the mGlu5 receptor antagonist, MPEP, whereas treatment with the mGlu5 receptor positive allosteric modulator (PAM), VU0360172, increased KCC2 expression. In contrast, pharmacological inhibition of mGlu1 receptors with JNJ16259685 enhanced cerebellar KCC2 protein levels and KCC2 immunoreactivity in Purkinje cells, whereas treatment with the mGlu1 receptor PAM, RO0711401, reduced KCC2 expression. To examine whether the reduction in KCC2 expression caused by the absence or the inhibition of mGlu5 receptors could affect GABAergic transmission, we performed electrophysiological and behavioral studies. Recording of extracellular action potentials in Purkinje cells showed that the inhibitory effect of the GABAA receptor agonist, muscimol, was lost in cerebellar slices prepared from mGlu5 −/− mice or from mice treated systemically with MPEP, in line with the reduction in KCC2 expression. Similarly, motor impairment caused by the GABAA receptor PAM, diazepam, was attenuated in mice pre-treated with MPEP. These findings disclose a novel function of mGlu5 receptors in the cerebellum and suggest that mGlu5 receptor ligands might influence GABAergic transmission in the cerebellum and affect motor responses to GABA-mimetic drugs. This article is part of the Special Issue entitled 'Metabotropic Glutamate Receptors, 5 years on'. Highlights: Group-I mGlu receptors regulate KCC2 expression in the cerebellum. KCC2 expression is largely reduced in Purkinje cells of mice lacking mGlu5 receptors. mGlu5 receptors modulate GABAA receptor-mediated responses in Purkinje cells.